Image politics in the Middle East : the role of the visual in political struggle - Khatib, Lina (Lina H.) (London ; : I.B. Tauris, 2013)
"Politics in the Middle East is now seen and the image is playing a central part in processes of political struggle. This is the first book in the literature to engage directly with these changing ways of communicating politics in the region {u2013} and particularly with the politics of the image, its power as a political tool."--From the publisher's website.
Part I: Revolutionary Illusions, 1. The Visual Legacy of the Cedar Revolution in Lebanon; 2. Hizbullah: Image Management and Political Survival; 3. The Politics of (In)visibility in Iran. -- Part II: Revolutionary Images, 4. The Visual Rush of the Arab Spring ; 5. Television Images and Political Struggle ; 6. From Images of Dictators to Images of Citizens.
boek
Keywords: Midden Oosten